IMAGING OF THE ANTERIOR COMMUNICATING ARTERY: NORMAL AND ABNORMAL FINDINGS RELATED TO ANEURYSM - Abdulloh, Arizal (Transpublika Publisher, 2023)
The anterior communicating artery (AComA) is a critical component of the Circle of Willis, serving as a vital conduit that connects the bilateral anterior cerebral arteries. This study aims to provide a comprehensive overview of the imaging characteristics of the AComA, encompassing both normal variations and abnormal findings associated with aneurysm development. Utilizing advanced imaging techniques, a thorough analysis of the AComA complex was conducted in a cohort of subjects. Normal anatomical variants were meticulously documented, highlighting variations in length, diameter, and branching patterns. Abnormal findings indicative of potential aneurysm markers was carefully assessed, encompassing variations in morphology, hemodynamic flow patterns, and wall integrity. Special attention was given to elucidate the factors contributing to aneurysm initiation within the AComA complex. The clinical significance of distinguishing between normal anatomical variations and potential pathological findings was underscored, emphasizing the critical importance of early detection and intervention to mitigate the risks associated with aneurysm rupture. The findings of this study contribute valuable insights to the field of neurovascular diagnostics and therapeutic strategies. By enhancing our understanding of the AComA and its role in aneurysm development, this research aims to empower clinicians with the knowledge needed for informed decision-making and proactive management. Ultimately, the comprehensive examination of AComA imaging, encompassing both normal and abnormal variants, holds the potential to drive advancements in cerebrovascular care and improve patient outcomes.